PENINGKATAN PREFERENSI MEREK PADA PRODUK KOSMETIK BERBASIS DESAIN KEMASAN VISUAL, KUALITAS PRODUK, SERTA NILAI PELANGGAN - Cempaka Paramita; Mochammad Farid Affandi; Fauzia Tysia Arini; Kristian Suhartadi Widi Nugraha (Management Insight: Jurnal Ilmiah Manajemen, 2022)
The world’s cosmetic industry, including Indonesia, has experienced significant development in recent years in line with the increasing consumption of cosmetic products. Manufacturers of local cosmetic brands have to face fierce competition from non-local brands. Therefore, it is necessary to increase consumer brand preference. This study analyzes the increase in brand preference based on visual packaging design, product quality, and customer value on Wardah, as one of the most liked and popular local cosmetic brands in Indonesia. The sample consisted of 150 respondents who were taken using purposive sampling technique. The data analysis method used in this study is multiple linear regression analysis of latent variables with a confirmatory approach or Confirmatory Factor Analysis (CFA). The results of this study indicate that visual packaging design, product quality, and customer value significantly increase brand preference.